Probiotics Clostridium butyricum and Bacillus subtilis ameliorate intestinal tumorigenesis. (September 2015) - Chen, Zhao-Fei; Ai, Luo-Yan; Wang, Ji-Lin; Ren, Lin-Lin; Yu, Ya-Nan; Xu, Jie; Chen, Hao-Yan; Yu, Jun; Li, Min; Qin, Wen-Xin; Ma, Xiong; Shen, Nan; et al.
Aims: To investigate the antitumor effects of probiotics Clostridium butyricum and Bacillus subtilis on colorectal cancer (CRC) progression.Materials & methods: The effects of C. butyricum and B. subtilis on CRC cells were studied. Male C57BL/6 mice with 1, 2-dimethylhydrazine dihydrochloride (DMH)-induced CRC were intervened by these two probiotics and the antitumor effects were examined by comparing the tumor incidence and detecting the inflammatory and immune-related markers.Results & conclusions:   C. butyricum and B. subtilis inhibited the proliferation of CRC cells, caused cell cycle arrest and promoted apoptosis. In vivo, these two probiotics inhibited the development of DMH-induced CRC. The molecular mechanism involved reduced inflammation and improved immune homeostasis. This work establishes a basis for the protective role of probiotics B. subtilis and C. butyricum in intestinal tumorigenesis.